ANALISIS FENOMENA JANUARY EFFECT TERHADAP RETURN PASAR DI BURSA EFEK INDONESIA (Riset Manajemen & Akuntansi, 2010)
The paper analyze about the seasonal anomaly called January effect, which occurs when the return on stock markets is highest and significant on January. The presence of these anomaly violates the weak form of market efficiency because returns are not random, but are predictable based on certain calendar effects. The objective of this paper is to test the existence of January effect in which sector on 9 sectors sectoral index in Indonesian Stock Exchange. Nine sector include: Agriculture, Mining, Basic industry, Miscellaneous industry, Property, Consumer Goods, Infrastructure, Finance, Trade and service. The sample used in this paper are stock market index at Indonesian Stock Exchange, with the proxy sectoral index, over 2001-2008. The results find thereâs one sector which show that January effect is exist, that sector is Consumer Goods Sector. The major conclusion of this paper shows that Indonesian stock market does not efficient on the weak form, one of the indicator is January effect phenomenon exist in Indonesian Stock Exchange which the stock returns are predictable based on certain calendar effect